Aratati ca:
a)![\frac{1- tg^{2}x }{1+ tg^{2}x }=cos2x \frac{1- tg^{2}x }{1+ tg^{2}x }=cos2x](https://tex.z-dn.net/?f=+%5Cfrac%7B1-+tg%5E%7B2%7Dx+%7D%7B1%2B+tg%5E%7B2%7Dx+%7D%3Dcos2x+)
b)
baiatul122001:
Pe b nu il mai faceti . l-am rezolvat
Răspunsuri la întrebare
Răspuns de
3
Salut,
![\dfrac{1-tg^2x}{1+tg^2x}=\dfrac{1-tg^2x}{1+\dfrac{sin^2x}{cos^2x}}=\dfrac{1-tg^2x}{\dfrac{cos^2x+sin^2x}{cos^2x}}=cos^2x(1-tg^2x)=\\\\\\=cos^2x-cos^2x\cdot tg^2x=cos^2x-sin^2x=cos(2x). \dfrac{1-tg^2x}{1+tg^2x}=\dfrac{1-tg^2x}{1+\dfrac{sin^2x}{cos^2x}}=\dfrac{1-tg^2x}{\dfrac{cos^2x+sin^2x}{cos^2x}}=cos^2x(1-tg^2x)=\\\\\\=cos^2x-cos^2x\cdot tg^2x=cos^2x-sin^2x=cos(2x).](https://tex.z-dn.net/?f=%5Cdfrac%7B1-tg%5E2x%7D%7B1%2Btg%5E2x%7D%3D%5Cdfrac%7B1-tg%5E2x%7D%7B1%2B%5Cdfrac%7Bsin%5E2x%7D%7Bcos%5E2x%7D%7D%3D%5Cdfrac%7B1-tg%5E2x%7D%7B%5Cdfrac%7Bcos%5E2x%2Bsin%5E2x%7D%7Bcos%5E2x%7D%7D%3Dcos%5E2x%281-tg%5E2x%29%3D%5C%5C%5C%5C%5C%5C%3Dcos%5E2x-cos%5E2x%5Ccdot+tg%5E2x%3Dcos%5E2x-sin%5E2x%3Dcos%282x%29.)
Simplu, nu ? :-).
Green eyes.
Simplu, nu ? :-).
Green eyes.
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă